Cascade Resonance Energy Transfer for the Construction of Nanoparticles with Multicolor Long Afterglow in Aqueous Solutions for Information Encryption and Bioimaging. Issue 10 (20th March 2022) - Mo, Luoqi; Liu, Hao; Liu, Zhiming; Xu, Xiaokai; Lei, Bingfu; Zhuang, Jianle; Liu, Yingliang; Hu, Chaofan
Abstract: There are still huge challenges in the development of carbon dots (CDs) based long afterglow materials with multicolor emissions, especially in aqueous solutions. This work reports a novel strategy of achieving of multicolor long afterglow in aqueous solution by incorporating phosphorescent CDs and fluorescent dyes into sub‐20 nm monodispersed silica nanoparticles. The silica matrix not only stabilizes the triplet excitons of CDs but also facilitates the efficient cascade Förster resonance energy transfer between the phosphorescent donor (CDs) and the energy acceptor (fluorescent dyes), which enables intensive multicolor long afterglow with adjustable wavelength from 510 to 610 nm and the largest Stokes shift of 255 nm. Based on these multicolor long afterglow nanoparticles, some time‐resolved, color multiple information encryptions are designed. By eliminating background noise, the signal‐to‐noise ratio of in vivo afterglow imaging is as high as 155.1 in the in vivo imaging system. Interestingly, the afterglow signal in mice can be easily and conveniently collected by the camera of cell phones, which may make in vivo bioimaging portable and inexpensive. This study will provide new ideas for the synthesis of multicolor CDs‐based long afterglow materials in solutions. Abstract : In this study, four colors of long afterglow materials in aqueous solution are developed by cascading energy transfer between phosphorescent carbon dots and different fluorescent dyes. These multicolor long afterglows have adjustable wavelengths from 510 to 610 nm and the maximum Stokes shift of 255 nm, so they show great potential for anti‐counterfeiting and high signal‐to‐noise ratio in vivo imaging.